Pengaruh Earnings Management terhadap Firms Value melalui Bankruptcy Risk sebagai Intervening Variabel pada Perusahaan yang terdaftar dalam Indeks Kompas 100 di Bursa Efek Indonesia - Marissa Angeliqna; Devie Devie (Business Accounting Review, 2016)
This study aimed to examine the direct and significant affect of earnings management to firms value, earnings management to bankruptcy risk and bankruptcy risk to firms value. The sample of this study was 43 companies listed in Kompas 100 Index in Indonesia Stock Exchange.This study used a quantitative approach, and the data were obtained from company’s financial statement. The data then processed by using smartPLS software. This study showed that there was negative and significant relationship of earnings management to firms value, positive and significant relationship between earnings management to bankruptcy risk and negative and significant relationship between bankruptcy risk to firms value.